LENGTH-WEIGHT RELATIONSHIP OF STREAKED GURNARD (Trigloporus lastoviza (BONNATERRE, 1788)) CAUGHT FROM NORTH-EASTERN MEDITERRANEAN - Basusta, Nuri; Basusta, Asiye; Sangün, Levent (E-Journal of New World Sciences Academy, 2018)
Aim of this study is to determine the length-weight relationships of streaked gurnard, Trigloporus lastoviza, caught from northeastern Mediterranean. T. lastoviza specimens were captured by commercial bottom trawler at depth of 155 to 212m off the Iskenderun Bay, Turkey. A total of 84 specimens (52 females and 32 males) were collected. Minimum-maximum length and weight of them were determined as 10.5-26.1cm and 5.92-163.8g for females and 6.41-22.0cm and 4.91-92.96g for males respectively. Length-weight relationships of T. lastoviza were found as W=0.0055*L3.104, R2=0.793, SEb=0.175 for all individuals, W=0.0076*L2.972, R2=0.84, SEb=0.258 for females and W=0.0076*L2.972, R2=0.75, SEb=0.245 for males. The type of growth for all inviduals, females and males were isometric growth (b=3).

Aim of this study is to determine the length-weight relationships of streaked gurnard, Trigloporus lastoviza, caught from northeastern Mediterranean. T. lastoviza specimens were captured by commercial bottom trawler at depth of 155 to 212m off the Iskenderun Bay, Turkey. A total of 84 specimens (52 females and 32 males) were collected. Minimum-maximum length and weight of them were determined as 10.5-26.1cm and 5.92-163.8g for females and 6.41-22.0cm and 4.91- 92.96g for males respectively. Length-weight relationships of T. lastoviza were found as W=0.0055*L3.104, R2=0.793, SEb=0.175 for all individuals, W=0.0076*L2.972, R 2=0.84, SEb=0.258 for females and W=0.0076*L2.972, R2=0.75, SEb=0.245 for males. The type of growth for all inviduals, females and males were isometric growth (b=3).
LENGTH-WEIGHT RELATIONSHIP OF STREAKED GURNARD (Trigloporus lastoviza (BONNATERRE, 1788)) CAUGHT FROM NORTH-EASTERN MEDITERRANEAN